O design colaborativo como possível ferramenta complementar a metodologia Lean startup - Ribeiro, Leonardo de Figueiredo. (2019)
In recent years solutions have emerged that are innovating and revolutionizing the world market through digital products or services. And the birth of these solutions has come mostly from product or service ideas that come to market through organizations called startups. Startups are temporary organizations characterized by uncertainty and high mortality risk in the early years of activity. And in order to try to overcome these difficulties, the lean startup methodology emerged. This methodology emphasizes a lean development model that is fast enough to launch minimum viable products for the solution hypothesis to be tested as soon as possible. The methodology has been an important tool for the success of startups. But over time, these startups are growing and increasing their staff and the number of processes, which can make them less efficient. So the big challenge is staying creative, not only in product or service innovation, but also in the company’s management processes and mechanisms. Collaborative design is a tool that can complement lean startup methodology and assist startups in this challenge. And this paper presents a research that verifies the complementation between the Lean startup methodology and the collaborative design.